"You Can't Really Hug a Tiger": Zookeepers and Their Bonds with Animals. (3rd September 2019) - Birke, Lynda; Hosey, Geoff; Melfi, Vicky
ABSTRACT: Zookeepers often report strong attachment (bonds) with animals in their care. This paper reports a qualitative study of how keepers perceived these animals; the aim was to explore keepers' experiences of bonding and how these related to the work done in zoos. Respondents were drawn from a large sample participating in a survey of zoo professionals; across five establishments, 14 volunteered. Semi-structured interviews were used; transcripts were subsequently analyzed and coded to identify key themes in the narratives. We identified four broad themes, the first being work: keepers enter the job for "love of animals" but also have to maintain physical and emotional distance from them in a zoo. The second theme was "specialness"; in particular, how keepers often saw themselves as the best person to deal with this or that individual animal. The third theme was how keepers drew boundaries: between species, and between "wild" and "tame." Keepers talk about animals as "wild" while also recognizing that in zoos these animals are captive. The fourth and main theme, however, was bonds: to which animals do keepers feel attachments, and why? And how might these impact the animals? These findings, which are consistent with the results of questionnaire-based studies, provide us with insights which can inform our judgments about the role of human– animal bond development in the management of zoo-housed animals.